2006
DOI: 10.2134/agronj2005.0241
|View full text |Cite
|
Sign up to set email alerts
|

Soil Tests for Predicting Corn Response to Nitrogen Fertilizer in New York

Abstract: The presidedress nitrate test (PSNT) is currently the best tool available for Northeastern producers to determine if corn (Zea mays L.) will benefit from sidedress N. The PSNT requires 0-to 30-cm soil samples, which can be difficult to obtain on stony soils, and samples need to be taken in late-spring, an inopportune time for dairy (Bos taurus) farmers. Additionally, the in-season nature of the PSNT prevents its use by producers who apply preplant broadcast N. The Illinois soil N test (ISNT) is a simple test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 21 publications
4
42
1
2
Order By: Relevance
“…Calibration curves were developed that identifi ed the ability of AH-N to predict the N rate required to achieve 95% RGY with the highest coeffi cients of determination occurring at the 0-to 30-cm depth for the ISNT (r 2 = 0.68) and the 0-to 45-cm depth for the DSD method (r 2 = 0.89). Th ese results are similar to the fi ndings for ISNT presented by other researchers for the calibration of N rate for corn (Klapwyk and Ketterings, 2006;Williams et al, 2007a). Previous work with the ISNT has resulted in a split decision on the method's predictive ability for N rate recommendations with several studies concluding that the ISNT was not an acceptable indicator for potentially mineralizable-N (Barker et al, 2006a;Laboski et al, 2008;Osterhaus et al, 2008;Spargo et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Calibration curves were developed that identifi ed the ability of AH-N to predict the N rate required to achieve 95% RGY with the highest coeffi cients of determination occurring at the 0-to 30-cm depth for the ISNT (r 2 = 0.68) and the 0-to 45-cm depth for the DSD method (r 2 = 0.89). Th ese results are similar to the fi ndings for ISNT presented by other researchers for the calibration of N rate for corn (Klapwyk and Ketterings, 2006;Williams et al, 2007a). Previous work with the ISNT has resulted in a split decision on the method's predictive ability for N rate recommendations with several studies concluding that the ISNT was not an acceptable indicator for potentially mineralizable-N (Barker et al, 2006a;Laboski et al, 2008;Osterhaus et al, 2008;Spargo et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…For an extensive set of on-farm response studies, Mulvaney et al (2006) found that test values were positively related to check-plot yield and negatively related to delta yield, EONR and fertilizer N-use effi ciency (FNUE) all at p < 0.001. Klapwyk and Ketterings (2006) were successful in using the ISNT to predict corn yield response to sidedress N in New York, but only when organic matter (OM) was considered. In contrast to these fi ndings, work from several other states including Iowa (Barker et al, 2006b), Wisconsin (Osterhaus et al, 2008), Virginia (Spargo et al, 2009), Michigan, Minnesota, and Nebraska (Laboski et al, 2008) reported that the ISNT could not accurately predict corn response to N. Th e primary concerns raised in the latter studies involve the relationships between ISNT hydrolyzed-N and total N (TN), crop response to N and EONR.…”
Section: Predicting Nitrogen Fertilizer Needs For Rice In Arkansas Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Isto porque, segundo Klapwyk & Ketterings (2006), a determinação do teor de nitrato no solo neste estádio do milho, que é chamado de teste de pré-aplicação de N em cobertura ("Pre-sidedress Nitrate Test"), é atualmente a melhor ferramenta disponível para os produtores da região Nordeste dos Estados Unidos da América (EUA) para determinar se o milho responderá à aplicação de N em cobertura. Este teste tem sido muito estudado, principalmente nos EUA, pois permite avaliar a variação da disponibilidade de N do solo durante o ciclo da cultura, determinando maior flexibilidade no manejo da adubação nitrogenada em situações específicas (Rambo et al, 2004).…”
Section: Resultsunclassified
“…Klapwyk and Ketterings (2006) similarly reported that ISNT-N alone also was not an effective predictor of corn silage dry matter yield in New York state; however, they suggested that critical soil test values could be developed when ISNT-N and SOM were considered together. The relationship of soil N measures to yield response was strengthened using piecewise regression analysis (Toms and Lesperance 2003) (Figs.…”
Section: Relationships Between Yield Parameters and Measures Of Soil mentioning
confidence: 99%